Determination of the experimental extinction coefficient of therapeutic proteins using the Edelhoch method. (June 2021) - Batabyal, Dipanwita; Lord, Harrison; Ahlstrom, Ben; Wikström, Mats
Abstract: The objective of this study was to determine how the theoretical values of the extinction coefficient (EC) compares to the experimentally determined extinction coefficient for a large set of biotherapeutic proteins measured by the Edelhoch method. We have performed extensive analysis based on over 176 observations covering 19 different types of molecules from different structural classes covering mAbs, bispecific antibodies, fusion proteins and BiTE molecules. Precision was measured by assessing the repeatability of the measurements for each molecule and determining the relative standard deviation (%RSD). The maximum RSD observed for any given molecule was 1.7% with an average RSD of 0.9%. Deviation from the theoretical extinction coefficient was determined by calculating the experimental bias first, which is the difference between the mean experimental extinction coefficient and the theoretical extinction coefficient. The percent bias (%bias) was then calculated as (bias ÷ theoretical EC) × 100. The maximum %bias observed for any given molecule was 5.3% with an average %bias of 2.6%. Our results indicate that the Edelhoch method is highly reliable with significant improvement in execution efficiency with reduction in cost, time and improvements in safety when compared to the commonly used methods such as amino acid analysis (AAA) technique.